Single-Bundle versus Double-Bundle Anterior Cruciate Ligament Reconstruction: A Prospective Randomized Controlled Trial with 6-Year Follow-up - Adravanti, Paolo; Dini, Francesco; de Girolamo, Laura; Cattani, Massimo; Rosa, Michele Attilio (The Journal of Knee Surgery, 2017)
Single-bundle (SB) anterior cruciate ligament (ACL) reconstruction is increasingly used in a large number of patients and it allows obtaining very good clinical and subjective results; however, functional tests show a persistent rotational instability. Biomechanical studies seem to indicate that double-bundle (DB) ACL reconstruction allows to obtain increased anterior and rotational stability compared with SB. The aim of this prospective randomized controlled study was to compare the clinical outcome and the possible osteoarthritic evolution of patients treated either with a SB (freehand transtibial femoral tunnel) or with a DB technique (outside-in for posterolateral femoral tunnel/inside-out for anteromedial femoral tunnel) at a final follow-up of 6 years. A total of 60 patients with complete ACL rupture (age, 16–40 years) were prospectively randomized to SB (n = 30) or DB (n = 30) groups. Patients were evaluated preoperatively and after surgery at 6 months, 1, 3, and 6 years with Lysholm score, International Knee Documentation Committee (IKDC) form, and KT-2000 (Medmetric Corp). The degree of osteoarthritis (OA) based on the Kellgren–Lawrence grade was also assessed. No significant differences in background factors between the two groups were observed. Homogeneity was also found in term of preoperative Lysholm score, IKDC, and KT-2000 between SB and DB groups. After 6 months from surgery, both groups showed significant improvements for Lysholm, IKDC, and KT-2000 score with respect to preoperative observations (p < 0.001); however, no significant differences have been observed in term of postoperative values between SB and DB groups at each time point (6-year evaluation: Lysholm score 98.14 ± 10.03 and 97.22 ± 12.82; IKDC normal + nearly normal 95 and 100%; KT-2000 1.68 ± 1.26 and 1.03 ± 1.92 for SB and DB, respectively; all p > 0.05). At the final follow-up, three patients (11.11%) in the DB group and two patients (7.69%) in the SB group presented signs of OA progression. Our study did not reveal any advantages in using DB ACL reconstruction in mid- to long-term follow-up in term of clinical outcome and knee stability, as well as in term of OA progression.
Keywords: anterior cruciate ligament (ACL); ligament tears; double bundle ACL reconstruction; single bundle ACL reconstruction; osteoarthritis